2005
DOI: 10.1097/01.pcc.0000170624.29667.7b
|View full text |Cite
|
Sign up to set email alerts
|

Liver support for fulminant hepatic failure: Is it time to use the Molecular Adsorbents Recycling System in children?*

Abstract: Although promising preliminary results suggest that MARS may have a significant position in the therapeutic arsenal for FHF, no sufficient data exist to justify its use in children. For as long as the results of the ongoing adult trial are not available, the indications of this expensive technique in children with FHF are limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…Artificial extracorporeal liver support devices were designed to improve the survival of patients with ALF by carrying out the detoxification processes, in the form of bridge therapy, while awaiting transplantation [14]. …”
Section: Discussionmentioning
confidence: 99%
“…Artificial extracorporeal liver support devices were designed to improve the survival of patients with ALF by carrying out the detoxification processes, in the form of bridge therapy, while awaiting transplantation [14]. …”
Section: Discussionmentioning
confidence: 99%
“…It is based on the principles of dialysis, filtration, and adsorption. A systematic review published last year concluded that liver support systems do not significantly affect mortality when compared with conventional medical therapy in children [44]. Another study involved 13 patients treated with MARS, with overall mortality of 85% in a setting without timely liver transplantation [45].…”
Section: Liver Support Systemsmentioning
confidence: 98%
“…[5][6][7] Extracorporeal liver support (ELS) is designed to improve the survival of patients with severe liver failure by replacing the detoxification function of the liver and thereby creating a bridge to transplantation. 8 ELS modalities include the fractionated plasma separation, adsorption, and dialysis system (Prometheus), 9,10 single-pass albumin dialysis, 11 and Molecular Adsorbent Recirculating System (MARS) albumin dialysis, which was introduced by Stange and Mitzner in the 1990s. [12][13][14] In 1999, MARS was shown to be effective in the clearance of protein-bound and water-soluble toxins and to have a positive effect on hepatic encephalopathy (HE) in 13 adult patients with acute-on-chronic liver failure (ACLF).…”
Section: See Editorial On Page 277mentioning
confidence: 99%